Toward a biosocial science : evolutionary theory, human nature, and social life - Riley, Alexander (London: Routledge, 2021)
"Towards a Biosocial Science is a critical introduction to the history and conceptual concerns of sociology that incorporates the immense and revolutionary contributions evolutionary biology, behavioral genetics, and neuroscience are making to the study of human behavior and social organization"--
Keywords: Sociology; Evolution (Biology); Neurosciences